Emulação dinâmica de fontes alternativas de energia utilizando um motor de indução - Berriel, Ryan Carlos de Oliveira (2019)
In this work, the use of a squirrel cage induction motor for emulation of mechan- ical dynamics resulting from renewable energy converters is presented. The method adopted depends on a precise induction motor torque control and information of the rotational speed derivative. For torque control, the vector control known as FOC (Field Oriented Control) was used. To determine the derivative of the speed a robust method was adopted based on sliding mode technique. Through the knowledge of velocity and its rate of variation it is possible to emulate the inertia and the viscous friction of the energy source. As an application, the concept is realized for the emulation of wave energy con- verter of the type Heaving Point Absorber and for emulation of wind turbines. Simulation and experimental results are presented for validation of developed models and controls.